Investigation Procedures for The Crime of Harming Public Funds (Raparin Journal of Humanities (RJH), 2025)
There is no doubt that the crime of harming public funds harms the state, the public interest, the system of society and its beliefs, or the lives or property of individuals, which must be protected and not neglected. The state and society are concerned that the crime of harming public funds and crimes of financial corruption remain subject to follow-up and prosecution, and that the perpetrator does not escape punishment in order to preserve the interest of the state, the public benefit, and the security and safety of society. Therefore, penal laws were established that undertake the task of protecting the public interests of the state and the security of society and controlling it by establishing a legal system that prohibits behavior and actions that threaten society with harm or expose its security to danger, by establishing and defining the forms of the crime. What increases the importance of the investigation procedures into the crime of harming public funds and the manner in which they are conducted is that they are in direct and constant contact with the rights and freedoms of employees and those charged with public service. This has prompted the legislature to regulate these procedures in legal texts. The legislature has surrounded these procedures with safeguards, controls, and restrictions that enhance their effectiveness and, as a result, lead to the rapid detection of the crime of harming public funds, both intentional and unintentional, as well as crimes of administrative and financial corruption. This does not allow those conducting the investigation to initiate investigative procedures and reach conclusions based on their own discretion or at the discretion of the investigator. Regulating criminal procedures in the investigation of the crime of harming public funds represents a form of coordination between the state, in achieving the public interest, and the interests of employees, in protecting their basic rights to freedom and peace of mind. This means that while the state's interest requires punishing the employee who committed the crime of harming public funds and their accomplices, it simultaneously requires preserving the freedoms and rights of employees. Once a complaint or report is filed, the procedural obstacle is removed through the investigating authorities, whether the Public Prosecution, the Integrity Commission, or others. These authorities regain their freedom to file criminal proceedings for the crime of harming public funds and to initiate all procedures related to accusation, investigation, and trial, while observing the principle of appropriateness. The purpose of the complaint or report is therefore to grant the investigating authorities permission to initiate criminal proceedings after the crime of harming public funds has been proven.